Web xKaliBurr: An Online Platform for Information Gathering in Pentest for Internet Applications - Barros, Daniel R.; Cabral, Lucas; Oliveira, João V. A.; Castro, Felipe M.; Soares, Lucas L.; Monteiro, José M.; Bento, Joaquim; Rocha, Lincoln S. (Journal of the Brazilian Computer Society, 2026)
The Information Gathering stage in web Pentests is crucial as it lays the foundation for all subsequent activities. However, comprehensive information gathering requires the manual use of various tools that demand advanced technical knowledge. In this context, we propose Web xKaliBurr, an open-source web tool that automates the information gathering stage of web Pentest. With a simple and user-friendly interface, the proposed tool performs extensive scans from the site's URL, providing a wide range of information and recommendations, allowing users without advanced knowledge to assess their site's security and detect potential flaws or vulnerabilities. To evaluate Web xKaliBurr, we applied the System Usability Scale (SUS) questionnaire to measure aspects of usability in accordance with the user's subjective assessment and the Net Promoter Score (NPS) method to measure user satisfaction and willingness to recommend it to others. This study involved 10 respondents. The SUS method had a score of 80, which indicates a good to excellent product, and the results of using NPS reached a value of 70%, reflecting a very good level of user satisfaction. Besides, we performed an evaluation with 3 experts in web Pentests.